BENTONIT TERAKTIVASI ASAM SULFAT SEBAGAI ADSORBEN DALAM PEMURNIAN PELUMAS BEKAS - Tiva Lathifah; Nia Yuliani; Gladys Ayu Paramita Kusumah Wardhani (Universitas Nusa Bangsa, 2019)
Activated Bentonits of Sulfatic Acid as Adsorben in Purchase of Used Lubricants Recycling of used lubricating oil is one of the alternatives in the framework of efficiency, saving oil consumption, and reducing pollution. One effort to purify used lubricating oil is to separate impurities through the adsorption method. The adsorbent that can be used is bentonite. Activation of bentonite using acid will produce adsorbent with an active side and greater surface acidity so that the adsorption ability is higher than before activated. Characteristics of lubricating oil produced are: kinematic viscosity 40 °C and 100 °C at 109.94 cSt and 14.57 cSt recently; viscosity index is 136; specific gravity 15 °C is 0.8872; and the resulting color is L5.0. Activated sulfonic bentonite can be an optimum adsorbent in purifying used lubricating oil, with optimum bentonite concentration is 30% and optimum adsorption temperature is 70 °C resulting in a 49% increase in viscosity efficiency of 40 °C and 30.79% for temperatures of 100 °C.Keywords: Bentonite, Lubricants, Adsorption ABSTRAK Daur ulang minyak pelumas bekas merupakan salah satu alternatif dalam rangka efisiensi, penghematan konsumsi minyak bumi, serta mengurangi pencemaran. Salah satu upaya menjernihkan minyak pelumas bekas adalah dengan memisahkan zat-zat pengotor melalui metode adsorpsi. Adsorben yang dapat digunakan adalah bentonit. Aktivasi bentonit menggunakan asam akan menghasilkan adsorben dengan sisi aktif dan keasaman permukaan yang lebih besar sehingga kemampuan adsorpsinya lebih tinggi dibandingkan dengan sebelum diaktivasi. Karakteristik minyak pelumas yang dihasilkan yaitu: viskositas kinematik 40 °C dan 100 °C sebesar 109,94 cSt dan 14,57 cSt secara berturut-turut; indeks viskositas sebesar 136; specific gravity 15 °C sebesar 0,8872; serta warna yang dihasilkan adalah L5,0. Bentonit teraktivasi asam sulfat mampu menjadi adsorben yang optimum dalam pemurnian minyak pelumas bekas, dengan konsentrasi bentonit optimum adalah 30% dan suhu adsorpsi optimum adalah 70 °C menghasilkan % efisiensi kenaikan viskositas sebesar 49,15% untuk suhu 40 °C dan 30,79% untuk suhu 100 °C.Kata kunci : adsorpsi, bentonit, pelumas